2024
DOI: 10.3390/jcm13061628
|View full text |Cite
|
Sign up to set email alerts
|

Association between Surrogate Markers of Insulin Resistance and the Incidence of Colorectal Cancer in Korea: A Nationwide Population-Based Study

Minkook Son,
Sang Yi Moon,
Myeongseok Koh
et al.

Abstract: Background: Insulin resistance (IR) is assessed using surrogate markers such as the triglyceride–glucose (TyG) index, the triglyceride-to-high-density lipoprotein cholesterol (TG/HDL-C) ratio, and the metabolic score for IR (METS-IR). Limited studies investigated their association with colorectal cancer (CRC) incidence, and no research has been conducted on their association with the METS-IR. Method: This study used claims data from the Korean National Health Insurance Service, analyzing a cohort of 314,141 Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…IR was reported to impact the incidence of several solid tumors, including colorectal, lung, and pancreatic cancer (14)(15)(16)(17). A previous study reported that thyroid volumes were larger, and the risk of thyroid nodules was higher in IR patients (18).…”
Section: Introductionmentioning
confidence: 99%
“…IR was reported to impact the incidence of several solid tumors, including colorectal, lung, and pancreatic cancer (14)(15)(16)(17). A previous study reported that thyroid volumes were larger, and the risk of thyroid nodules was higher in IR patients (18).…”
Section: Introductionmentioning
confidence: 99%